Uji Aktifitas Antihiperglikemia Ekstrak Etanol 70% Echinometra mathaei Pada Tikus Putih Jantan Galur Wistar Yang Diinduksi Aloksan - Kresnamurti, Angelica; Suresti, Suresti; Hamid, Iwan Sahrial (Universitas Muhammadiyah Gresik, 2020)
Abstract : Sea urchin (Echinometra mathaei) contains a compound of Echinochrome A, which is a polyhydroxy naphthoquinone that is known to be potential antioxidant. The antioxidant effect correlated with the antidiabetic activity that associated with oxidative stress conditions. The aim of this study was to determine the effect of 70% Ethanol Extract of sea urchin (Echinometra mathaei) on blood glucose levels in alloxan induced rats. This research was an experimental study using 30 male white rats, divided into 6 groups, i.e the negative control group (normal rat were only given CMC Na 0,5%), Positive control group (hyperglycemic rats were only treated with CMC Na 0,5%), metformin group as a refference standard group (hyperglycemic rats that treated with metformin) and the treatment group (hyperglycemic rats were treated with ethanol extract 70% of Echinometra mathaei dose of 100 mg/kgBW, 200 mg/kgBW and 400 mg/kgBW). Alloxan monohidrat 120 mg/KgBW was used as diabetogen agent. The parameters examined in this study were blood glucose levels of rats after 7 days of treatment. The observational data were analyzed using the One Way ANOVA (P < 0.05) and continued with LSD. The results of this study showed that all doses of ethanol extract significantly reduced blood glucose levels in rats compared to the control group. The most effective dose in reducing blood glucose levels and compared to metformin was 400 mg / kgBW. Key word: alloxan induced, Echinometra mathaei, ethanol 70%, hiperglycemia, marine product.